Multidrug-resistant extended-spectrum beta-lactamase-producing Escherichia coli in poultry and cattle farms in India: Prevalence and survey-based risk factors - Hina Malik; Randhir Singh; Simranpreet Kaur; Neha Parmar; Anuj Tyagi; R.S. Aulakh; Jatinder Paul Singh Gill (Journal of Global Antimicrobial Resistance)
Objective: Unregulated use of antibiotics in animal-production leads to the emergence of multidrug-resistant (MDR) bacteria, including extended-spectrum beta-lactamase-producing Escherichia coli (ESBL E. coli), posing significant public health threats. This study aimed to assess and compare the role of cattle and poultry, along with farmworkers, in the emergence and spread of ESBL E. coli using a human-animal interface approach in One-Health framework. Methods: Twenty cattle and 20 poultry farms in Ludhiana, India, were surveyed to determine antibiotic usage and biosecurity in farms. Animal faeces/poultry droppings, farmworkers hand swabs, and stool samples were examined for the presence of ESBL E. coli. The isolates were screened for antibiotic susceptibility and antimicrobial resistance genes. Generalized linear mixed models explored the variations in ESBL E. coli prevalence based on farm animal species, practices, and biosecurity measures. Results: A higher prevalence of ESBL E. coli was identified in poultry (63.5%) compared to cattle (46%) and farmworkers (12%), which aligns with higher antibiotic use in poultry (85%) than cattle (70%). Most isolates (86.52%) were MDR, with poultry farm isolates having 97% MDR and 90.7% carrying the blaCTXM gene. Generalized linear mixed models analysis revealed improved biosecurity and low antibiotic use were associated with lower ESBL E. coli prevalence. Conclusions: This study highlights cattle and poultry farms as reservoirs for MDR and ESBL E. coli, contributing to rising environmental burden of antimicrobial resistance genes. It underscores the need to reduce antibiotic use in animal farming, particularly poultry, to address emerging antibiotic resistance and protect both animal and human health.